English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

if the answer is 8x^3(3-x) all over 3(2-x^3)^2

2006-11-25 21:17:01 · 6 answers · asked by Mikaela 1 in Science & Mathematics Mathematics

6 answers

[(x^3)/(2 - x)]^4/3
dy/dx = (4/3)[(x^3)/(2 - x)]^1/3[3x^2(2 - x) + (x^3)]/(2-x)^2
dy/dx = (4)[(x^3)/(2 - x)]^1/3[6x^2 - 3x^3 + (x^3)]/(3(2-x)^2)
dy/dx = 8x^3(3 - x)/(3(2-x)^7/3)

2006-11-25 22:34:39 · answer #1 · answered by Helmut 7 · 0 0

to derivate equation form u^n derivative = n (u^n-1) du/dx

d/dx f(x) = 4/3 * [(x^3)/2 -x ]^1/3 * (3/2 x^2-1)
= [(x^3)/2 -x ]^1/3*(2x^2-4/3)= 2[(x^3)/2 -x ]^1/3*(x^2-2/3)

2006-11-26 05:27:28 · answer #2 · answered by maussy 7 · 0 0

y=[(x^3)/2-x]^4/3

use the chan rule.

y=(4/3)(x^3)/2-x}^1/3[ (3x^2/2)-1]

2006-11-26 06:12:14 · answer #3 · answered by amila 1 · 0 0

combine quotient and power rule

2006-11-26 05:22:40 · answer #4 · answered by RichUnclePennybags 4 · 0 0

question is not understandable please rewite in detail

2006-11-26 05:25:33 · answer #5 · answered by sidharth 2 · 0 0

can you please rewrite your question!

2006-11-26 05:22:16 · answer #6 · answered by polizei 2 · 0 0

fedest.com, questions and answers